The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.16966/2379-7150.130
|View full text |Cite
|
Sign up to set email alerts
|

Masgutova Neurosensorimotor Reflex Integration (MNRI) Neuromodulation Technique induces Positive Brain Maps (QEEG) Changes

Abstract: Masgutova Neurosensorimotor Reflex Integration MNRI® is a non-invasive method for evaluating and improving neurodevelopmental delays in children having neurological dysfunctions such as cerebral palsy (CP), Autistic Spectrum Disorders (ASD), and other types of neurological dysfunctions. Changes in the reflex patterns of 53 individuals with CP and other types of brain damage were used as objective measures. They were evaluated before and after participation in an intensive MNRI® rehabilitation treatment for 8 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The MNRI therapy program is based on the theory that impaired reflex circuits can be reconstructed and re-integrated, which involves awakening the sensorimotor genetic memory in individuals even with severe diagnosis (such as CP and brain damage) [57,58]. MNRI is an evidence-and research-based therapeutic program which utilizes neuroplasticity via reflex integration techniques for the neuro-sensorimotor-cognitive development of children and adults with neuro deficits and learning problems [61,62]. Over the past 30 years, numerous studies were conducted and many articles demonstrating the efficiency of the method were published by Dr. S. Masgutova and her scientific colleagues from various international institutions.…”
Section: Mnri Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNRI therapy program is based on the theory that impaired reflex circuits can be reconstructed and re-integrated, which involves awakening the sensorimotor genetic memory in individuals even with severe diagnosis (such as CP and brain damage) [57,58]. MNRI is an evidence-and research-based therapeutic program which utilizes neuroplasticity via reflex integration techniques for the neuro-sensorimotor-cognitive development of children and adults with neuro deficits and learning problems [61,62]. Over the past 30 years, numerous studies were conducted and many articles demonstrating the efficiency of the method were published by Dr. S. Masgutova and her scientific colleagues from various international institutions.…”
Section: Mnri Methodsmentioning
confidence: 99%
“…Exercise-based program MNRI is based on the technique called "repatterning" which essentially means re-educating, recoding, rerouting, and paving the reflex nerve pathways specific for dynamic and postural reflex schemes (e.g., Babinski, Automatic Gait, Bauer Crawling, Hands Grasp, and others) [61]. The stimulation of reflex pathways is aimed at strengthening and stabilizing the traces of genetic sensory-motor memory and at the activation of the innate defense mechanisms through the body's neuroendocrine hormonal 'alarm' system (HPA axis) (hypothalamus-pituitary-adrenal gland stress response cycle activation) in times of stress or danger [20].…”
Section: Mnri Methodsmentioning
confidence: 99%
“…Masgutova Neurosensorimotor Reflex Method (MNRI) addresses the neurosensorimotor aspect of early sensory-motor patterns and reflexes to support sensory-motor integration and neurodevelopment of children and adults with neurodeficits and learning challenges: CP, TBI [5] [6] [7] [8], ASD [9] [10] Down syndrome [11] [12] [13] [14] [15] and other [16] [17]. MNRI therapy meets the ever-increasing demands for neurorehabilitation of individuals with impaired sensorimotor functions due to damage or dysfunctions in central nervous systems.…”
Section: Introductionmentioning
confidence: 99%
“…MNRI therapy meets the ever-increasing demands for neurorehabilitation of individuals with impaired sensorimotor functions due to damage or dysfunctions in central nervous systems. Previous studies of the MNRI Method and its different sub-programs demonstrated a positive effect on immune markers [13] [18] [19], neurophysiological functions [7] [8] and different developmental aspects including the regulation of behavior and emotions, language, and communication [9] [17] [20] [21]. This paper presents a study of the effectiveness of MNRI therapy using neurotransmitter analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation